COVID-19 Pandemic Once Again Exposes the Weakest Link in Laboratory Services: Specimen Delivery - Lapić, Ivana (Lab Med, 2020)
OBJECTIVE: Reorganization of the emergency department (ED) during the COVID-19 pandemic implied closure of the ED-dedicated laboratory and manual transport of all specimens to the dislocated central laboratory. The impact of such reorganization on laboratory turnaround time (TAT) was examined. METHODS: The TAT from blood sampling to specimen reception (TAT1), from specimen reception to test reporting (TAT2), and from sampling to test reporting (TAT3) were compared between the pandemic peak month in 2020 and the same month in 2019. We evaluated whether TAT2 fulfills the recommended 60-minute criteria. RESULTS: A statistically significant difference was observed for all comparisons (P <.001), with TAT1 prominently contributing to TAT3 prolongation (from 48 minutes to 108 minutes) and exceeding the recommended 60-minute criteria. The TAT2 was extended from 33 minutes to 49 minutes. CONCLUSION: An ED reorganization compromised the usual laboratory services for patients in the ED, with manual specimen delivery being the main cause for TAT prolongation.